Arduino-based Automatic Light Switching System - Li Moqi; Zhang Ziqian; Yin Haocheng; Liu Chang-huan; Jiang Feng-min (E3S Web of Conferences, 2023)
This article focuses on the problem of high power consumption caused by long working hours of lights, and designs an automatic light switch system based on the number of people to achieve energy-saving effects. After experiencing the process of selecting hardware, designing circuits, writing programs, structural design, 3D modeling, 3D printing processing, assembly, etc., an automatic light on/off system has been designed, which is low-cost and can achieve automatic light on/off based on Arduino microcontroller technology, playing a role in saving electricity to a certain extent.